Respect in the Commonwealth: A toolkit for building relationships, generating new ideas and increasing respect - Secretariat, Commonwealth (Commonwealth iLibrary, 2022)
This 'project in a box' on building resilience and inter-community dialogue encompasses detailed instructions, illustrations, and inspiration. The toolkit focuses on how to deliver workshops on inter- and intra-community relationship building, and aims to improve global citizenship literacy, awareness of tools and learning of skills to build socially cohesive and tolerant communities that are resilient to violent extremism. This toolkit is for anyone who feels motivated to improve relationships and respect in the community, the workplace and even among friends and family. You can use it to improve respect generally or to tackle a specific issue, such as hate speech or inter-ethnic conflict. Depending on your level of experience of bringing people together, and the kinds of issues you are working with, you will find a range of different tools to apply. Whether you are experienced in facilitating change or are just starting out, this toolkit has been designed and tested for you.